Plusiodonta casta (Butler, 1878) (Lepidoptera, Erebidae, Calpinae) found in West Sayan (Central Siberia, Russia) - Oleg E. Kosterin; Svyatoslav A. Knyazev (Acta Biologica Sibirica, 2024)
The first record of Plusiodonta casta (Butler, 1878) from West Sayan Mountains in Siberia based on photographic observation is presented. The new finding is located ca 3,000 km to the west from the previously known distribution area of the species. The possible origin of the species population in Siberia is discussed.